2021
DOI: 10.1186/s12879-021-06568-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and clinical evaluation of a rapid antibody lateral flow assay for the diagnosis of SARS-CoV-2 infection

Abstract: Background The novel coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which has quickly spread worldwide since its outbreak in December 2019. One of the primary measures for controlling the spread of SARS-CoV-2 infection is an accurate assay for its diagnosis. SARS-CoV-2 real-time PCR kits suffer from some limitations, including false-negative results in the clinic. Therefore, there is an urgent need for the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The viral antigens obtained after concentration and purification of SARS-CoV-2 inactivated by the different chemical reagents evaluated in this study were submitted to 10% SDS-PAGE and showed similar protein band profiles, suggesting homogeneity in the macrostructure of the viral proteins recovered after the different virus treatments, such as the suggestive molecular weight for the M protein of about 25 kda, the N-protein with about 46-58 kDa, the S2 subunit, which can be presented with 50.3-64.5 kDa, the subunit S1 around 67-85 kDa, as well as S-dimer around 180-200 kDa and S-trimer around 250 kDa ( Bosch et al, 2003 , Kuo et al, 2016 , Ke et al, 2020 , Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The viral antigens obtained after concentration and purification of SARS-CoV-2 inactivated by the different chemical reagents evaluated in this study were submitted to 10% SDS-PAGE and showed similar protein band profiles, suggesting homogeneity in the macrostructure of the viral proteins recovered after the different virus treatments, such as the suggestive molecular weight for the M protein of about 25 kda, the N-protein with about 46-58 kDa, the S2 subunit, which can be presented with 50.3-64.5 kDa, the subunit S1 around 67-85 kDa, as well as S-dimer around 180-200 kDa and S-trimer around 250 kDa ( Bosch et al, 2003 , Kuo et al, 2016 , Ke et al, 2020 , Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the 13 selected studies, 10 presented high values of sensitivity and specificity (>80%) [56][57][58]60,61,[64][65][66][67][68], and 1 reported 100% of sensitivity and specificity [56]. Lower sensitivity values were observed in the first days after infection [57,61,62,64] than the days postinfection.…”
Section: Immunoglobulin Detection Testsmentioning
confidence: 99%
“…Regarding immunoglobulin detection tests, we identified nine studies that assessed IgM and IgG levels [56][57][58][59][60][61][62][63][64], three evaluating only IgG [65][66][67], and one evaluating IgA, IgG, and IgM [68]. A total of 10 antibody tests were performed by lateral-flow assays (considering gold and fluorescence assays) [57][58][59][60][61][62][63][64][65]68], 1 by electrochemical enzyme immunoassay (ELISA) [56], 1 by magnetofluidic immuno-PCR platform [66], and 1 by the Split Luciferase (spLUC) antibody sensor [67].…”
Section: Immunoglobulin Detection Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, detection of nAb is time-consuming and harbors a number of technical pitfalls [ 2 ]. Therefore, simplified and point-of-care accessible assays such as lateral flow immunoassays (LFIAs) might represent a valuable alternative [ 3 , 4 ]. The performance of these tests can vary greatly and should be examined in detail before use [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%